2009
DOI: 10.17221/15/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exposure to bifenthrin on some haematological, biochemical and histopathological parameters of rainbow trout (Oncorhynchus mykiss)

Abstract: AbstrAct:The effect of the pyrethroid, bifenthrin, on rainbow trout (Oncorhynchus mykiss) was assessed based on biochemical, haematological and histopathological examination of fish exposed to Talstar 10 EC pesticide preparation (active substance 100 g/l bifenthrin) at a concentration of 14.7 µg/l. There was a significant (P < 0.01) decrease in plasma ammonia, and significant (P < 0.01) increase in glucose, creatine kinase, alkaline phosphatase and lactate dehydrogenase. Haematologically, fish showed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 24 publications
6
36
1
2
Order By: Relevance
“…In rodents, the dominant phase I metabolic reaction for triazine pesticides is cytochrome P450-mediated N-dealkylation (Hanioka et al, 1999 a,b). Triazine pesticides have a direct effect on kidney structure and function in freshwater fish (Velisek et al, 2008(Velisek et al, , 2009b. In our experiment, the caudal kidney of carp with chronic exposure to simazine showed destruction of the tubules, although chronic exposure to terbutryn had no effect on caudal kidney.…”
Section: Triazinesmentioning
confidence: 42%
See 2 more Smart Citations
“…In rodents, the dominant phase I metabolic reaction for triazine pesticides is cytochrome P450-mediated N-dealkylation (Hanioka et al, 1999 a,b). Triazine pesticides have a direct effect on kidney structure and function in freshwater fish (Velisek et al, 2008(Velisek et al, , 2009b. In our experiment, the caudal kidney of carp with chronic exposure to simazine showed destruction of the tubules, although chronic exposure to terbutryn had no effect on caudal kidney.…”
Section: Triazinesmentioning
confidence: 42%
“…During the laboratory toxicity test, common carp exposed to terbutryn and simazine showed normal feeding habits and exhibited no abnormal behaviour. Velisek et al (2009b) reported accelerated respiration and loss of movement coordination in rainbow trout and carp following acute poisoning with metribuzin. These characteristics have also been reported in Oreochromis niloticus and Chrysichthyes auratus (Hussein et al, 1996) and in Carassius auratus by Saglio & Trijasse (1998) following acute poisoning with atrazine.…”
Section: Triazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Degeneration of hepatocytes has been described after exposure of bifenthrin and cyhalothrin (Velisek et al 2009a;Velisek et al 2009b;Richterova et al 2014), and damage of gill lamellae was de- scribed (Velisek et al 2006;Velisek et al 2009a). The concentration of 3.14 µg/l cypermethrin in the form of Alimethrine 10 EM was found to be associated with fatty degeneration of liver and severe teleangioectasiae of gills in juvenile rainbow trout (O. mykiss) (Velisek et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Estas observaciones coinciden con lo encontrado por otros autores para exposiciones agudas y subagudas de piretroides en peces (El-Sayed y Saad 2007, Velíšek et al 2009b). Es de resaltar que estas manifestaciones suelen ser irreversibles si el nivel de toxicidad supera el umbral máximo de exposición y acumulación (Herwig 1979).…”
Section: Discussionunclassified